INCLUSIVE EDUCATION: PEDAGOGICAL METHODS FOR WORKING WITH CHILDREN WITH DISABILITIES - Xolboev Asqarali Mirxoldorovich (Journals Park Publishing, 2025)
This article analyzes the concept of inclusive education, its significance, and the pedagogical methods used in working with children with disabilities. It is emphasized that in the process of inclusive education, it is important to take into account the individual needs of each child, provide them with equal opportunities and ensure their social adaptation. The article presents modern pedagogical tendencies and methods, as well as recommendations for teachers.